2019
DOI: 10.29333/aje.2019.424a
|View full text |Cite
|
Sign up to set email alerts
|

Description of Students' Scientific Literacy Competencies on the Scientific Issue of Flat Earth Theory

Abstract: Scientific literacy is one of the basic competencies that must be possessed in the XXI century. These competencies include explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting scientific data and facts. These three competency indicators must be embedded in students to help them to solve problems and give the best responding to issues especially science issues, as well as "flat earth theory". The purpose of this study was to describe students' scientific literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Scientific literacy is one of the topics in science education capable of dealing with technological developments, such as answering hoaxes about science and technology (Widayoko, Femilia, Lesmono, Sudjatmi, Prastiwi, & Munfarikha, 2019). Various information, either true or false, is accessible every day.…”
Section: Performance Of Gifted Young Scientist Candidates Based On Grade Levelmentioning
confidence: 99%
“…Scientific literacy is one of the topics in science education capable of dealing with technological developments, such as answering hoaxes about science and technology (Widayoko, Femilia, Lesmono, Sudjatmi, Prastiwi, & Munfarikha, 2019). Various information, either true or false, is accessible every day.…”
Section: Performance Of Gifted Young Scientist Candidates Based On Grade Levelmentioning
confidence: 99%
“…Dalam kajian akademik, Studi-studi terkait gagasan Bumi Datar umumnya cenderung mengaitkannya dengan teori konspirasi, misalnya, tentang NASA yang memalsukan pendaratan di bulan (Landrum, A. R., & Olshansky, 2019), (Mohammed, 2019), (Olshansky, 2018), (Paolillo, 2018), (Runnels, 2019) dan edukasi sains (Melo, L. W. S. de, Passos, M. M., & Salvi, 2020), (Widayoko, A., Femilia, P. S., Lesmono, A. D., Sudjatmi, H., Prastiwi, V. D., & Munfarikha, 2019), (Ozsoy, 2012). Beberapa pengamat lainnya mengaitkan gagasan Bumi Datar dengan landasan epistimologis (Purwanto, 2017), (Djamaluddin, 2018).…”
Section: Pendahuluanunclassified
“…This socio-constructivist approach require the construction of knowledge by learners which can only be effectively achieved if teachers have a mastery of the nature of science (NOS) or scientific literacy. According to Widayoko et al (2019) developing scientific literacy in learners is one of the basic competencies of the 21st century. Unfortunately, most studies have shown that science teachers have an inadequate knowledge about NOS (Buaraphan, 2010;Dogan & Abd-ElKhalick, 2008;Lederman, 2007;Seung et al, 2009;Jatsho & Dorji, 2022, Wangdi et al, 2019.…”
Section: Introductionmentioning
confidence: 99%